Research collaboration on community health worker programmes in low-income countries: an analysis of authorship teams and networks - Elma Nelisiwe Maleka; Paul Currie; Helen Schneider (Taylor & Francis Group, 2019)
Background: Global health research partnerships, which promote the exchange of ideas, knowledge and expertise across countries, are considered key to addressing complex challenges facing health systems. Yet, many studies report inequalities in these partnerships, particularly in those between high and low-and-middle-income countries (LMICs). Objective: This paper examines global research collaborations on community health worker (CHW) programmes, specifically analysing the structures of authorship teams and networks in publications reporting research on CHW programmes in low-income countries (LICs). Methods: A sub-set of 206 indexed journal articles reporting on CHW programmes in LICs was purposefully selected from a prior review of research authorship on CHW programmes in all LMICs over a five year period (2012-2016). Data on country and primary organisational affiliation and number of publications for all individual authors, programme area (e.g. maternal child health) and total citations per paper were extracted and coded in excel spreadsheets. Data were then exported and analysed in Stata/ICV.14 and Gephi. Results: The 206 papers were authored by 1045 authors from 299 institutions, based in 43 countries. Half (50.1%) the authors came from LIC-based institutions, 43.8% from high-income country (HIC) institutions, 2.9% from middle-income country (MIC) institutions and 3.2% had different first affiliations in different publications. Authors based in the USA (302) and UK (68) accounted for just over a third (35.4%) of all authors. Partnership patterns revealed a primary mode of North-South collaboration with authors from the US, and to a lesser extent the UK, playing central bridging roles between institutions. Strong network clusters of multiple-affiliated authors were evident in research on MCH and HIV/TB aspects of CHW programmes. Conclusion: Knowledge production on CHW programmes in LICs flows predominantly through a pool of connected HIC authors and North-South collaborations. There is a need for strategies harnessing more diverse, including South-South, forms of partnership.